Pengaruh Dewan Direksi Asing, Kesibukan Dewan Direksi, dan Keberagaman Gender terhadap Kebangkrutan Perusahaan: Studi Empiris pada Perusahaan Sektor Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2021 – 2023 - Kuswara, Febi Ayu Lisna; Afriyenti, Mayar (Universitas Negeri Padang, 2025)
This study examines the influence of foreign directors, board busyness, and gender diversity on corporate bankruptcy in consumer cyclicals companies listed on the Indonesia Stock Exchange between 2021 to 2023. The research is motivated by the increasing number of bankruptcy cases despite stable economic indicators, highlighting the role of corporate governance characteristics in financial distress. The study aims to determine whether specific board attributes affect the likelihood of bankruptcy. Using purposive sampling, the study analyzed 231 firm-year observations from 77 companies. The Springate model was employed to assess bankruptcy risk, while panel data regression with the random effect model was used to test the hypotheses. The findings reveal that foreign board membership, board busyness, and gender diversity do not have a statistically significant effect on bankruptcy risk. These results suggest that these board characteristics alone may not determine a firm’s financial stability in the context of Indonesian consumer-driven industries. To advance this line of inquiry, future research is encouraged to include broader governance variables such as audit committee size, managerial ownership, and audit quality to better reflect internal control mechanisms.